Ethical issues in international research and multicentre studies - DOI: 10.3395/reciis.v2.Sup1.206en - Udo Schüklenk; Darragh Hare (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
This article provides an overview of the key issues pertaining to international research and multicentre studies, with particular emphasis to international biomedical research in the developing world. The article begins with a brief explanation of the regulations governing international biomedical research and an exposition of the debate surrounding the standards of care that should be provided by research conducted in the developing and developed countries. The article describes the issues involved in the participation of vulnerable groups in research, with specific reference to developing countries. Eventually, the article considers matters related to emergency and post-trial care, exploitation, reward and undue inducement, voluntariness and benefits to local communities.